Lipid rafts as signaling hubs in cancer cell survival/death and invasion: implications in tumor progression and therapy - Mollinedo, Faustino; Gajate, Consuelo (Journal of lipid research, 2020)
Cholesterol/sphingolipid-rich membrane domains, known as lipid rafts or membrane rafts, play a critical role in the compartmentalization of signaling pathways. Physical segregation of proteins in lipid rafts may modulate the accessibility of proteins to regulatory or effector molecules. Thus, lipid rafts serve as sorting platforms and hubs for signal transduction proteins. Cancer cells contain higher levels of intracellular cholesterol and lipid rafts than their normal non-tumorigenic counterparts. Many signal transduction processes involved in cancer development (insulin-like growth factor system and phosphatidylinositol 3-kinase-AKT) and metastasis [cluster of differentiation (CD)44] are dependent on or modulated by lipid rafts. Additional proteins playing an important role in several malignant cancers (e.g., transmembrane glycoprotein mucin 1) are also being detected in association with lipid rafts, suggesting a major role of lipid rafts in tumor progression. Conversely, lipid rafts also serve as scaffolds for the recruitment and clustering of Fas/CD95 death receptors and downstream signaling molecules leading to cell death-promoting raft platforms. The partition of death receptors and downstream signaling molecules in aggregated lipid rafts has led to the formation of the so-called cluster of apoptotic signaling molecule-enriched rafts, or CASMER, which leads to apoptosis amplification and can be pharmacologically modulated. These death-promoting rafts can be viewed as a linchpin from which apoptotic signals are launched. In this review, we discuss the involvement of lipid rafts in major signaling processes in cancer cells, including cell survival, cell death, and metastasis, and we consider the potential of lipid raft modulation as a promising target in cancer therapy.